Chapter Chinese returnee students and cultural production: the case of ex-students of Opera in Italy - Rizzuto, Giuseppe (Studi e saggi, 2023)
The aim of this chapter is to point out the connection between mobility and cultural activities of Chinese returnee opera students. Many Chinese students in Italy attend cultural and artistic university courses. They may be considered significant in analyzing Chinese reverse migration from Italy. The examined connection involves several dynamics, including artistic aspects, historical reasons, social and economic changes, public policies and consumerism styles. Mobility and cultural production may be analyzed through both a structural and imaginative dimension. The structural dimension is composed of international agreements, global mobility law conditions, social and economic changes, and private investments in education to accumulate cultural capital that produce (or reproduce) certain social structures and experiences. On the other hand, the imaginative dimension is shaped by the lifestyle adopted by middle class families, including their work activities and cultural consumption. Returnee students are both the subjects who promote this process and the object of this dynamic. Chinese singers of Italian opera, upon graduating university in Italy, join the possibilities of the work field-in Bourdieu's perspective-which is formed by the two aforementioned dimensions. Finally, perceived differences between Italy and China in terms of musical technique and culture are reworked according to contemporary cultural policies.